Review on Content Based Medical Image Retrieval System and Techniques (International Journal of Engineering and Computer Science, 2017)
The rapid expansion and improvement in medical science and technology which generates the amount of image data more and more in its regular activity such as CT-image, X-ray, MRI etc. Due to scalability of image data, it has been increased in size of database and containing millions of images. For the proper management of medical image and requirement of efficient retrieval system for clinical decision making and research activities, It emerges Content based medical image retrieval system for quick diagnosis of medical images. The review of CBMIR system has been analyzed the overview of currently available techniques useful for medical domain.